QoS-Guaranteed Cross-Layer Adaptive Transmission Algorithms with Selective ARQ for the IEEE 802.16 OFDMA System - Filin, S.A.; Moiseev, S.N.; Kondakov, M.S.; Garmonov, A.V.; Savinkov, A.Y.; Yun Sang Park; Do Hyon Yim; Jae Ho Lee; Seok Ho Cheon; Ki Tae Han (IEEE Vehicular Technology Conference, 2006)
We consider the IEEE 802.16 OFDMA system with the frequency diversity frame structure. We perform adaptive coding and modulation, allocation of the time-frequency resource and transmit power to the downlink and uplink service flows, scheduled for transmission in the current frame. We also adapt the position of the frame boundary between the uplink and downlink subframes. We propose three heuristic algorithms that minimize the total power transmitted in both downlink and uplink subframes subject to the maximum transmission power constraints and the available time-frequency resource constraint, while satisfying the QoS requirements for all downlink and uplink service flows scheduled for transmission. Our algorithms take into account the MAC and PHY layers processing in case of ARQ. We evaluate the proposed heuristic algorithms by the system level simulation of the IEEE 802.16 network.